2009
DOI: 10.1063/1.3073051
|View full text |Cite
|
Sign up to set email alerts
|

Nanometer range correlations between molecular orientations in liquids of molecules with perfect tetrahedral shape: CCl4, SiCl4, GeCl4, and SnCl4

Abstract: Neutron and x-ray weighted total scattering structure factors of liquid carbon, silicon, germanium, and tin tetrachlorides, CCl(4), SiCl(4), GeCl(4), and SnCl(4), have been interpreted by means of reverse Monte Carlo modeling. For each material the two sets of diffraction data were modeled simultaneously, thus providing sets of particle coordinates that were consistent with two experimental structure factors within errors. From these particle configurations, partial radial distribution functions, as well as co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 23 publications
4
54
0
Order By: Relevance
“…Actually, the heights of the FSDP in S N ( Q ) are greater than those in S X ( Q ). Not only glasses, but also the molecular liquids CCl 4 , SiCl 4 , GeCl 4 , and SnCl 4 with the regular X Cl 4 tetrahedral anion ( X  = C, Si, Ge, and Sn) have a similar FSDP at approximately Q  = 1.2 Å −1 , despite these liquids not having the interconnections of regular X Cl 4 tetrahedral anions27. Although the relationship between the FSDP and the topology of the network is still not well understood, it is suggested that a pseudo network of P-P correlations contributes to the stabilization of the glassy structure.…”
Section: Resultsmentioning
confidence: 99%
“…Actually, the heights of the FSDP in S N ( Q ) are greater than those in S X ( Q ). Not only glasses, but also the molecular liquids CCl 4 , SiCl 4 , GeCl 4 , and SnCl 4 with the regular X Cl 4 tetrahedral anion ( X  = C, Si, Ge, and Sn) have a similar FSDP at approximately Q  = 1.2 Å −1 , despite these liquids not having the interconnections of regular X Cl 4 tetrahedral anions27. Although the relationship between the FSDP and the topology of the network is still not well understood, it is suggested that a pseudo network of P-P correlations contributes to the stabilization of the glassy structure.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4] It is of interest though to proceed to a direct comparison of both liquids in order to ascertain whether there might be any relevant quantitative difference. This will also provide a basic framework for the comparative study of the rest of the liquids to be reported in the next section.…”
Section: Methane Versus Carbon Tetrachloridementioning
confidence: 99%
“…This finding has very recently been corroborated in a reverse Monte Carlo ͑RMC͒ analysis of combined neutron and ͑new͒ x-ray scattering measures. 2 As this methodology is not limited to this phase and/or compound, it has also been applied to investigate the similarities and differences between the liquid and plastic phases for both carbon tetrachloride and neopentane 3 and to the gas-liquid coexistence line for carbon tetrachloride; 4 recently, Pusztai et al applied this methodology to tin iodide 5 and several chlorinated compounds. 2,6 In order to complete the program outlined in Ref.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations